Violenza di genere e identità delle donne - Maggiorelli, Simona (Il sogno della farfalla, 2020)
This article introduces a monographic issue on the topic of gender based violence and its historical and cultural roots. The author offers an interpretation of this phenomenon highlighting the contrast between the dramatic frequency of feminicides and gender based violence in Italy with its related cultural and legislative backwardness.